INDUSTRIAL PLANNING IN LESS DEVELOPED COUNTRIES: On the role of informal sector in urban context - Rully Damayanti (Dimensi: Journal of Architecture and Built Environment, 2002)
In many Third World cities, the approach to industrial planning is adapted from developed countries. Planning system may conflict with the dynamics of an informal sector where priorities are directed to the fundamentals of survival in an often competitive and hostile working environment. It is important for Third World’ governments to identify planning approaches that respect the current condition of land use occupation. Modernization of traditional or informal sectors may develop integrated linkages with the formal sector creating opportunities land use integration between these sectors.